STEROIDS FROM THE SUPER RED DRAGON FRUIT (Hylocereus costaricensis) - Supriadi, H.; Salam, S.; Abdullah, F. F.; Subarnas, A.; Sidik, R.; Supratman, U.; Shiono, Y. (Jurnal Kimia (Journal of Chemistry); Vol.13 No.2 Juli 2019DO - 10.24843/JCHEM.2019.v13.i02.p17, 2019)
Two steroids compounds, 7 ? -Hydoxy ? -sitosterol ( 1 ) and ? -sitosterol ( 2 ), have been isolated from ethyl acetate extract of the fresh Super Red Dragon Fruit ( Hylocereus costaricensis ).The chemical structure of compounds 1 and 2 were identified by spectroscopic data including UV, IR, NMR-1D, NMR-2D  and mass as well as by comparing  with previously reported spectral data. Compounds 1 and 2 were reported for the first time from dragon fruit ( Hylocereus costaricensis ). Keywords : 7 ? -Hydoxy ? -sitosterol, ? -sitosterol , Hylocereus costaricensis , steroids.